Toxicological Evaluation of Vanillin Flavor in E-Liquid Aerosols on Endothelial Cell Function: Findings from the Replica Project - R. Emma; A. Sun; K. Partsinevelos; S. Rust; V. Volarevic; R. Lesmana; A. Giordano; H. Goenawan; M. I. Barliana; A. Arsenijevic; N. Kastratovic; V. Markovic; et al. (Cardiovascular Toxicology, 2026)
There are challenges that require collaboration among researchers to ensure that tobacco harm reduction strategies are evidence-based. A key challenge is evaluating the safety of flavors in e-cigarettes. Many flavorings are deemed “generally recognized as safe” (GRAS) for ingestion, but this does not guarantee their safety when inhaled. The Replica international research group is dedicated to the replication of studies on tobacco alternatives. As part of this effort, the group conducted a conceptual replication of the vanillin-specific experiments from the study by Fetterman et al. (2018), with the goal of validating their conclusions regarding this compound. We used Aspire Zelos 3 e-cigarette and prepared e-liquids containing propylene glycol, vegetable glycerin, and vanillin. The e-liquids were vaporized under regular (1 Ohm coil, 14 watts) and sub-Ohm (0.3 Ohm coil, 200 °C) settings using a vaping machine, following ISO20768:2018 puffing regime. The vapor was collected into a trapping solution to prepare aqueous extracts for treating human aortic endothelial cells. We evaluated cytotoxicity, oxidative stress, nitric oxide bioavailability, and inflammation addressing some gaps reported in the original study. We observed some harmful effects mostly attributable to ethanol used to trap vanillin, but no harmful effects from vanillin. Our results confirm the endothelial cell dysfunction observed in the original paper, but clarify that these effects are mainly attributable to ethanol and not to vaporized vanillin, indicating that, under the experimental conditions applied, vanillin does not elicit significant adverse effects on vascular endothelial cells. However, further research is needed to confirm its toxicological profile. Graphical Abstract Created in BioRender. https://BioRender.com/rn8dt1m .

From magma to macrophage: the grand challenges of volcanic environments - Catherine A. Mériaux; Edward Ntim Gasu; Guillaume Nyagatare; Vicky Ruganzu; Philbert Ntivuguruzwa; Mwumvaneza Mutagoma; Atalay Ayele; Julyan H. E. Cartwright; Valérie Cayol; Laurent Charlet; Claudia Corradino; Antonio Costa; et al. (Bulletin of Volcanology, 2026)
The interdisciplinary study of volcanic processes, which extend across all timescales and lengths, requires a multitude of approaches, ranging from analogue and numerical modelling to observations and fieldwork and extending to mathematics. A conference was held at the East African Institute for Fundamental Research, affiliated with the University of Rwanda, a country which, along with the Democratic Republic of Congo, presents a unique geodynamic context. Located along the East African Rift, an active seismic region, Rwanda is close to two of Africa's most active volcanoes, including Nyiragongo, which overlooks Lake Kivu, a deep volcanic lake rich in dissolved carbon dioxide and methane, the latter of which is used for electricity generation. In this context, the conference addressed many “classic” volcanological topics and their modern advances, such as multiphase lava flows, subsurface magma propagation, seismic and deformation signals from a volcano, modelling of volcanic emission dispersion, and volcanic lakes. Yet, it broadened the discussion to the volcanic particle-water interface and its impact on soils, volcanoes and climate change, and volcanoes and health. This article aims to highlight and share the richness of the integration and interconnectedness of the various questions related to a volcanic environment, as well as their impact on society. Ultimately, this conference also demonstrated the importance of promoting science in Africa and developing countries so that the next generation of African researchers is equipped to address the challenges facing their nations.

Fossil billfish (Xiphioidei) from the Eocene of Hampden, North Otago, New Zealand - Seabourne Rust; Morne Wium; Rodrigo A. Otero; Marianna Terezow (Gondwana Research, 2026)

From ocean to screen: Data gaps, conservation concerns, and sustainability challenges in Germany’s online marine ornamental fish trade - Nora Leonie Rust; Jacqueline Jürgens; Rikke Oegelund Nielsen; Johanna Staerk; Morgane Tidière; Dalia A. Conde (Journal for Nature Conservation, 2025)

Impacts of deforestation on drought patterns across multiple time scales in Europe: insights from LUCAS regional climate models - Yan Li; Bo Huang; Diana Rechid; Peter Hoffmann; Lisa Jach; Kirsten Warrach-Sagi; Marcus Breil; Priscilla A. Mooney; Merja Tölle; Rita M. Cardoso; Henning W. Rust (Journal of Hydrology, 2025)

P18-20 Building Bridges in Tobacco Harm Reduction: A Global Interlaboratory Initiative for Standardized Smoke and Aerosol Exposure Assessment - M. Caruso; R. Emma; P. Zuccarello; S. Rust; G. Carota; K. Poulas; F. Zadjali; A. Sun; V. Volarevic; R. Lesmana; M. Tobi; K. Mesiakaris; et al. (Toxicology Letters, 2025)

P18-17 No Evidence of E-Cigarette Aerosol-Induced Cisplatin Resistance in Head and Neck Cancer Cells: Findings from the Replica International Study Group - G. Carota; R. Emma; K. Partsinevelos; S. Rust; A. Sun; A. Giordano; V. Volarevic; R. Lesmana; H. Goenawan; M.I. Barliana; A. Arsenijevic; N. Kastratovic; et al. (Toxicology Letters, 2025)

Effect of intertidal air exposure and handling husbandries on shell development, meat condition and survival of farmed Pacific oysters (Magallana gigas, Thunberg 1793) - Ernest O. Chuku; Gregory G. Smith; Debashish Mazumder; Steven A. Rust; Andrew J. Trotter (Aquaculture, 2025)

P01-33 Toxicity induced by cigarette smoke and electronic cigarette aerosols - K. Partsinevelos; R. Emma; A. Distefano; G. Carota; S. Rust; R. Pulvirenti; D. Campagna; R. Polosa; M. Caruso; G. Li Volti (Toxicology Letters, 2024)

The vascular gene Apold1 is dispensable for normal development but controls angiogenesis under pathological conditions - Zheng Fan; Raphaela Ardicoglu; Aashil A. Batavia; Ruslan Rust; Lukas von Ziegler; Rebecca Waag; Jing Zhang; Thibaut Desgeorges; Oliver Sturman; Hairuo Dang; Rebecca Weber; Martin Roszkowski; et al. (Angiogenesis, 2023)
The molecular mechanisms of angiogenesis have been intensely studied, but many genes that control endothelial behavior and fate still need to be described. Here, we characterize the role of Apold1 (Apolipoprotein L domain containing 1) in angiogenesis in vivo and in vitro. Single-cell analyses reveal that - across tissues - the expression of Apold1 is restricted to the vasculature and that Apold1 expression in endothelial cells (ECs) is highly sensitive to environmental factors. Using Apold1 −/− mice, we find that Apold1 is dispensable for development and does not affect postnatal retinal angiogenesis nor alters the vascular network in adult brain and muscle. However, when exposed to ischemic conditions following photothrombotic stroke as well as femoral artery ligation, Apold1 −/− mice display dramatic impairments in recovery and revascularization. We also find that human tumor endothelial cells express strikingly higher levels of Apold1 and that Apold1 deletion in mice stunts the growth of subcutaneous B16 melanoma tumors, which have smaller and poorly perfused vessels. Mechanistically, Apold1 is activated in ECs upon growth factor stimulation as well as in hypoxia, and Apold1 intrinsically controls EC proliferation but not migration. Our data demonstrate that Apold1 is a key regulator of angiogenesis in pathological settings, whereas it does not affect developmental angiogenesis, thus making it a promising candidate for clinical investigation.

Implications of fire-induced evapotranspiration shifts for recharge-runoff generation and vegetation conversion in the western United States - Natalie M. Collar; Brian A. Ebel; Samuel Saxe; Ashley J. Rust; Terri S. Hogue (Journal of Hydrology, 2023)

Have farmers had enough of experts? - Niki A. Rust; Petra Stankovics; Rebecca M. Jarvis; Zara Morris-Trainor; Jasper R. de Vries; Julie Ingram; Jane Mills; Jenny A. Glikman; Joy Parkinson; Zoltan Toth; Regina Hansda; Rob McMorran; et al. (Environmental Management, 2022)
The exponential rise of information available means we can now, in theory, access knowledge on almost any question we ask. However, as the amount of unverified information increases, so too does the challenge in deciding which information to trust. Farmers, when learning about agricultural innovations, have historically relied on in-person advice from traditional ‘experts’, such as agricultural advisers, to inform farm management. As more farmers go online for information, it is not clear whether they are now using digital information to corroborate in-person advice from traditional ‘experts’, or if they are foregoing ‘expert’ advice in preference for peer-generated information. To fill this knowledge gap, we sought to understand how farmers in two contrasting European countries (Hungary and the UK) learnt about sustainable soil innovations and who influenced them to innovate. Through interviews with 82 respondents, we found farmers in both countries regularly used online sources to access soil information; some were prompted to change their soil management by farmer social media ‘influencers’. However, online information and interactions were not usually the main factor influencing farmers to change their practices. Farmers placed most trust in other farmers to learn about new soil practices and were less trusting of traditional ‘experts’, particularly agricultural researchers from academic and government institutions, who they believed were not empathetic towards farmers’ needs. We suggest that some farmers may indeed have had enough of traditional ‘experts’, instead relying more on their own peer networks to learn and innovate. We discuss ways to improve trustworthy knowledge exchange between agricultural stakeholders to increase uptake of sustainable soil management practices, while acknowledging the value of peer influence and online interactions for innovation and trust building.

Large silicic magma bodies and very large magnitude explosive eruptions - R. S. J. Sparks; J. D. Blundy; K. V. Cashman; M. Jackson; A. Rust; C. J. N. Wilson (Bulletin of Volcanology, 2022)
Over the last 20 years, new concepts have emerged into understanding the processes that lead to build up to large silicic explosive eruptions based on integration of geophysical, geochemical, petrological, geochronological and dynamical modelling. Silicic melts are generated within magma systems extending throughout the crust by segregation from mushy zones. Segregated melt layers become unstable and can assemble into ephemeral upper crustal magma chambers rapidly prior to eruption. In the next 10 years, we can expect major advances in dynamical models as well as in analytical and geophysical methods, which need to be underpinned in field research.

Contrasting mechanisms of magma fragmentation during coeval magmatic and hydromagmatic activity: the Hverfjall Fires fissure eruption, Iceland - E. J. Liu; K. V. Cashman; A. C. Rust; A. Höskuldsson (Bulletin of Volcanology, 2017)

MeMoVolc consensual document: a review of cross-disciplinary approaches to characterizing small explosive magmatic eruptions - L. Gurioli; D. Andronico; P. Bachelery; H. Balcone-Boissard; J. Battaglia; G. Boudon; A. Burgisser; M. R. Burton; K. Cashman; S. Cichy; R. Cioni; A. Di Muro; et al. (Bulletin of Volcanology, 2015)

Evolution of crust- and core-dominated lava flows using scaling analysis - Angelo Castruccio; A. C. Rust; R. S. J. Sparks (Bulletin of Volcanology, 2013)

Utilization of Biochar in Sugarcane and Sugar-Industry Management - R. G. Quirk; L. Van Zwieten; S. Kimber; A. Downie; S. Morris; J. Rust (Sugar Tech, 2012)

Multiphase petrography of volcanic rocks using element maps: a method applied to Mount St. Helens, 1980–2005 - D. D. Muir; J. D. Blundy; A. C. Rust (Bulletin of Volcanology, 2012)

Movements of hatchery-reared lingcod released on rocky reefs in Puget Sound - Jonathan S. F. Lee; Barry A. Berejikian; Michael B. Rust; Ken Massee; Terry Wright; Kyle Brakensiek; Scott Steltzner; H. Lee Blankenship (Environmental Biology of Fishes, 2011)

The −112G > A polymorphism of the secretoglobin 3A2 (SCGB3A2) gene encoding uteroglobin-related protein 1 (UGRP1) increases risk for the development of Graves’ disease in subsets of patients with elevated levels of immunoglobulin E - Dimitry A. Chistiakov; Natalia V. Voronova; Rust I. Turakulov; Kirill V. Savost’anov (Journal of Applied Genetics, 2011)

Effects of biochar from slow pyrolysis of papermill waste on agronomic performance and soil fertility - L. Van Zwieten; S. Kimber; S. Morris; K. Y. Chan; A. Downie; J. Rust; S. Joseph; A. Cowie (Plant and Soil, 2010)

Competition in mixed stands of beech and spruce: effects of climate and ozone - S. Rust; A. Roloff (European Journal of Forest Research, 2009)

Multiple origins of obsidian pyroclasts and implications for changes in the dynamics of the 1300 B.P. eruption of Newberry Volcano, USA - A. C. Rust; K. V. Cashman (Bulletin of Volcanology, 2007)

Uptake of erythromycin by first‐feeding sockeye salmon, Oncorhynchus nerka (Walbaum), fed live or freeze‐dried enriched adult Artemia or medicated pellets - M A Cook; M B Rust; K Massee; T Majack; M E Peterson (Journal of Fish Diseases, 2003)
The potential to use adult Artemia to deliver erythromycin to first‐feeding sockeye salmon, Oncorhynchus nerka (Walbaum), was investigated in three trials. In the first trial, first‐feeding sockeye were fed live erythromycin enriched adult Artemia or pellets containing equal amounts of erythromycin for 35 days. At the end of the trial, tissue erythromycin concentration of the fish fed the live Artemia was significantly greater ( P μ g mL −1 ; mean ± SEM), than the tissue concentration of the fish fed the pellets (0.72 ± 0.01 μ g mL −1 ). In the second trial, first‐feeding sockeye were fed either live or freeze‐dried bioencapsulated erythromycin (adult Artemia ) or pellets containing erythromycin daily for 21 days. Mean daily erythromycin concentration in fish fed the freeze‐dried Artemia , live Artemia , or pellets did not differ significantly. In the third trial, apparent erythromycin digestibility was determined. Significantly more ( P Artemia (live or freeze‐dried) appears to be greater than uptake from pellets. Freeze‐dried and live Artemia were equally effective at delivery suggesting enriched freeze‐dried adult Artemia could be produced into a highly palatable, consistent, off‐the‐shelf product.

Bioencapsulation of five forms of erythromycin by adult Artemia salina (L.) - M A Cook; M B Rust (Journal of Fish Diseases, 2002)
Uptake of five chemical forms of erythromycin by adult Artemia salina (L.) (erythromycin phosphate – EP, erythromycin stearate – ES, erythromycin estolate – EE, erythromycin hydrate – EH and crystalline erythromycin – CE) was investigated in two trials. In each trial, final erythromycin concentration in Artemia tissue and survival after a 12‐h bioencapsulation period were determined. In the first trial, Artemia tissue concentration after a 12‐h bioencapsulation period was significantly ( P −1 , mean ± SEM) ≈ EH (61.2 ± 3.4 μg mL −1 ) > CE (37.1 ± 10.7 μg mL −1 ) > EP (16.4 ± 7.7 μg mL −1 ) > control. In trial 2, Artemia tissue concentration was also significantly ( P −1 ) > CE (89.1 ± 1.7 μg mL −1 ) > ES (78.9 ± 1.6 μg mL −1 ) > EP (33.4 ± 5.2 μg mL −1 ) > control. Survival was significantly affected by erythromycin form in trial 1 with EP=control (100 ± 0.0%) > ES (74.4 ± 2.0%) > CE (32.2 ± 0.3%) > EH (8.8 ± 4.4%). In trial 2, survival was also significantly affected by erythromycin form with EP=control (100 ± 0.0%) > ES (67.1 ±3.7%) > CE (52.5 ± 7.7%) > EE (5.0 ± 2.5%). Based on both uptake and survival, EP and ES appear to be appropriate compounds for bioencapsulation of erythromycin using live adult Artemia .

Postglacial fault movement and palaeoseismicity in western Scotland: A reappraisal of the Kinloch Hourn fault, Kintail - Iain S. Stewart; Callum R. Firth; Derek J. Rust; Philip E.F. Collins; Judith A. Firth (Journal of Seismology, 2001)

Mapping porosity variation in a welded pyroclastic deposit with signal and velocity patterns from ground-penetrating radar surveys - A. C. Rust; J. K. Russell (Bulletin of Volcanology, 2001)